Utazási irodák utazásszervezői tevékenységének elemzése - Heizer Blanka (2015)
My thesis is about the history of tourism and the functioning of the Jakab Reisen travel agency. I spent my internship at this agency and while there, I monitored the com-plex tasks executed by the employees. I had some opportunity to serve the people who wanted to use the services of the agency. While writing my thesis, I analysed the needs and habits of the clients of the agency. On one hand, I drew conclusions about which routes attract passengers and to what extent; on the other hand, I observed that travel habits are strongly influenced by the financial status of the passengers. Tourists deprive themselves of unforgettable and wonderful experiences because the programs have high costs. I noticed that there are a lot of passengers who would be able to pay for even the most expensive facultative programs, but this segment of the clients seems to be less interested in fine arts and historical ruins. I have concluded that with the growing internet access the role of travel agencies will be-come limited and altered. If they want to continue functioning, they will have to find new services to offer in order to attract new clients.